Sustainability Reporting, Governance, Firm Size, and Firm Value - Eny Maryanti; Sucik Nurul Aini; Sarwenda Biduri (Journal of Accounting Science, 2026)
General Background: The food and beverage manufacturing sector supports Indonesia’s economy, while firm value remains critical because it reflects investor confidence and corporate sustainability. Specific Background: During 2021–2024, variations in price-to-book value and profitability indicated unstable market valuation despite attention to sustainability and governance practices. Knowledge Gap: Previous studies report inconsistent findings on the effects of sustainability reporting, managerial ownership as a proxy for good corporate governance, and firm size on firm value. These relationships have often been examined separately, leaving limited evidence on profitability’s differing moderating roles in Indonesian food and beverage companies. Objective: This study examines the direct effects of sustainability reporting, managerial ownership, and firm size on firm value and evaluates profitability as a moderator. Methods: Secondary data from 13 companies listed on the Indonesia Stock Exchange during 2021–2024 produced 52 firm-year observations selected through purposive sampling. The variables were measured using a sustainability disclosure index, managerial ownership ratio, natural logarithm of total assets, return on assets, and price-to-book value. Fixed-effects panel regression and Moderated Regression Analysis were performed using EViews 10. Results: Sustainability reporting and managerial ownership have insignificant effects on firm value, whereas firm size has a negative and significant effect. Profitability positively strengthens the sustainability reporting–firm value relationship, negatively weakens the managerial ownership–firm value relationship, and does not moderate the firm size–firm value relationship. Novelty: The findings reveal profitability’s contrasting moderating role. Implications: Companies should support sustainability disclosure with strong financial performance, while investors should assess profitability, governance, asset efficiency, and market valuation.